Toll-Like Receptors of Deuterostome Invertebrates - Satake, Honoo; Sekiguchi, Toshio (Frontiers in Immunology, 2012)
Defensive systems against pathogens are responsible not only for survival or lifetime of an individual but also for the evolution of a species. Innate immunity is expected to be more important for invertebrates than mammals, given that adaptive immunity has not been acquired in the former. Toll-like receptors (TLRs) have been shown to play a crucial role in host defense of pathogenic microbes in innate immunity of mammals. Recent genome-wide analyses have suggested that TLR or their related genes are conserved in invertebrates. In particular, numerous TLR-related gene candidates were detected in deuterostome invertebrates including a sea urchin (222 TLR-related gene candidates) and amphioxus (72 TLR-related gene candidates). Molecular phylogenetic analysis verified that most of sea urchin or amphioxus TLR candidates are paralogous, suggesting that these organisms expanded TLR-related genes in a species-specific manner. In contrast, another deuterostome invertebrate, an ascidian, Ciona intestinalis, was found to possess only two TLR genes. Moreover, Ciona TLRs, Ci-TLR1 and -2, were shown to possess “hybrid” functionality of mammalian TLRs. Such functionality of Ci-TLRs could not be predicted by sequence comparison with vertebrate TLRs, indicating the confounding evolutionary lineages of deuterostome invertebrate TLRs or their candidates. In this review article, we present recent advances in studies of TLRs or their candidates of deuterostome invertebrates, and provide insight into an evolutionary process of TLRs.